Incidence and Intensity of Catastrophic Health-care Expenditure for Type 2 Diabetes Mellitus Care in Iran: Determinants and Inequality - Piroozi B; Mohamadi-Bolbanabad A; Moradi G; Safari H; Ghafoori S; Zarezade Y; Bidarpour F; Rezaei S (Diabetes, Metabolic Syndrome and Obesity, 2020)
Bakhtiar Piroozi,1 Amjad Mohamadi-Bolbanabad,1 Ghobad Moradi,1 Hossein Safari,2 Shahnaz Ghafoori,1 Yadolah Zarezade,1 Farzam Bidarpour,1 Satar Rezaei3 1Social Determinants of Health Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, Iran; 2Health Promotion Research Center, Iran University of Medical Science, Tehran, Iran; 3Research Center for Environmental Determinants of Health, Health Institute, Kermanshah University of Medical Sciences, Kermanshah, IranCorrespondence: Satar RezaeiResearch Center for Environmental Determinants of Health, Health Institute, Kermanshah University of Medical Sciences, Kermanshah, IranEmail satarrezaei@gmail.comBackground: The present study aimed to assess the prevalence and intensity of catastrophic health-care expenditures (CHE) relating to type 2 diabetes mellitus care and inequality in facing such expenditures in Iran.Methods: A total of 1065 type 2 diabetes patients were included in this cross-sectional study. A multistage sampling method was used to select the samples. Data on sociodemographic characteristics, economic status, health and diabetic costs were collected using a self-constructed questionnaire. We used capacity to pay (CTP) of households to calculate the incidence of CHE due to diabetic care at four different thresholds. The mean positive overshoot (MPO) and overshoot were used to assess the intensity of CHE. The relative concentration index and slope index of inequality (SII) were used to measure socioeconomic-related inequalities in incidences of CHE. In addition, decomposition methods were used to identify the main factors affecting observed inequality in CHE.Results: The incidence of CHE at the 10, 20, 30, and 40% of CTP thresholds for type 2 diabetes mellitus care was 57.5, 28.9, 16.5, and 11.4%, respectively. The results of CI and SII indices for CHE due to diabetic care indicated that the incidence of CHE was more prevalent among patients with lower socioeconomic groups. The decomposition analysis showed that the socioeconomic status, marital status and gender of patients were the main factors contributing to socioeconomic inequality in incidence of CHE among the poor.Conclusion: Our study demonstrated that the incidence and intensity of CHE due to diabetic care were relatively high, particularly among socioeconomically disadvantaged patients. Modification to the present health care financing strategies is recommended in order to protect lower socioeconomic groups against the financial burden of diabetic care.Keywords: catastrophic cost, diabetes, inequalities, socioeconomic status